Immunogenicity of intranasal vaccine based on SARS-CoV-2 spike protein during primary and booster immunizations in mice - Huijie Yang; Ying Xie; Shuyan Li; Chunting Bao; Jiahao Wang; Changgui Li; Jiaojiao Nie; Yaru Quan (Human Vaccines & Immunotherapeutics)
Mucosal immunity plays a crucial role in combating and controlling the spread of highly mutated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Recombinant subunit vaccines have shown safety and efficacy in clinical trials, but further investigation is necessary to evaluate their feasibility as mucosal vaccines. This study developed a SARS-CoV-2 mucosal vaccine using spike (S) proteins from a prototype strain and the omicron variant, along with a cationic chitosan adjuvant, and systematically evaluated its immunogenicity after both primary and booster immunization in mice. Primary immunization through intraperitoneal and intranasal administration of the S protein elicited cross-reactive antibodies against prototype strains, as well as delta and omicron variants, with particularly strong effects observed after mucosal vaccination. In the context of booster immunization following primary immunization with inactivated vaccines, the omicron-based S protein mucosal vaccine resulted in a broader and more robust neutralizing antibody response in both serum and respiratory mucosa compared to the prototype vaccine, enhancing protection against different variants. These findings indicate that mucosal vaccination with the S protein has the potential to trigger a broader and stronger antibody response during primary and booster immunization, making it a promising strategy against respiratory pathogens.